O desequilíbrio econômico financeiro do contrato de concessão por inadimplemento do usuário como critério objetivo e legitimador da interrupção do serviço público à luz dos princípios do estado constitucional de direito - Almeida, Fabrício Bolzan de (2020)
The present doctoral thesis was divided into three parts: Part I - Public Service; Part II - Continuity of the Public Service; and Part III - Legitimizing Criterion of Public Service Interruption in light of the Constitutional Principles of the Democratic Rule of Law. In the first part, we approached the constitutional and infraconstitutional foundations of the public service institute and brought the main definitions brought by the administrativist doctrine, besides our conceptualization proposal. We also demonstrate the legal regime of public law and the importance of the French School of Law for the construction of the notion of public service. In the second part of this thesis we will address a point of extreme relevance, the principle of continuity of public service. To this end, we address the notions of consumer and user of the public service, as well as the main differences between tariffs and fees with respect to the kind of remuneration for public services. We will bring to the collation the view of contemporary national doctrine on the possibility or not of interruption of public service due to the default of the user, as well as the dominant position and exceptions in the jurisprudence of the Superior Court of Justice. The final part of this thesis will be elaborated in order to build what we defend as an objective criterion and legitimizing the interruption of the public service due to user default, considered the interest of the community, as determined by the General Law on Concessions and Permissions of Services. In the light of the Constitutional Principles of the Democratic Rule of Law. Therefore, we will re-read the principle of supremacy of the public interest as the superiority of fundamental rights and close the thesis with the philosophical foundation based on the theory of Tércio Sampaio Ferraz Júnior about the calibration rules. Field research conducted at the largest utility company in the country will also be presented